The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1111/j.1365-2265.1978.tb01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function Tests in Patients on Long‐term Treatment With Various Anticonvulsant Drugs

Abstract: Thyroid function tests were studied in patients undergoing long-term treatment with various anticonvulsant drugs. Previous reports that diphenylhydantoin induces a decrease in the serum concentrations of total and free thyroxine (T4) and triiodothyronine (T3) without a change in the TSH concentration were confirmed. Diphenylhydantoin had no effect on reverse T3. Carbamazepine was also found to decrease serum T4, the free T4 index and T3 but, with the exception of T3, the decrease was smaller than that induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
48
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 21 publications
12
48
1
Order By: Relevance
“…In this cohort, it has been shown that TH profiles in subjects without anti-epileptic drugs (AEDs) were comparable with the general population. However, AEDs were strongly associated with decreased T 4 , free T 4 (FT 4 ), T 3 , and rT 3 levels which is in agreement with other studies (24,25,26). It has been speculated that the changed thyroid parameters in patients that use AEDs can be explained by an influence of AEDs on binding proteins (27), a stimulation of hepatic degradation or conjugation of TH (28) or an altered peripheral deiodinase activity (23).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this cohort, it has been shown that TH profiles in subjects without anti-epileptic drugs (AEDs) were comparable with the general population. However, AEDs were strongly associated with decreased T 4 , free T 4 (FT 4 ), T 3 , and rT 3 levels which is in agreement with other studies (24,25,26). It has been speculated that the changed thyroid parameters in patients that use AEDs can be explained by an influence of AEDs on binding proteins (27), a stimulation of hepatic degradation or conjugation of TH (28) or an altered peripheral deiodinase activity (23).…”
Section: Introductionsupporting
confidence: 79%
“…Due to the observational nature of this study, it is very difficult to draw any conclusions on the causative or mechanistic features of these results. It is very well possible, although speculative, that AEDs interfere with the transport, metabolism, or excretion of trace elements, as is described for TH (23,24,25,26,27,28). Furthermore, although the generalizability of our findings may be limited, it is important to be aware of confounders if Se or Cu levels are analyzed in subjects on commonly prescribed AEDs.…”
Section: Figurementioning
confidence: 99%
“…28,29 Valproate on the other side showed no significant change in the serum T3, T4 and TSH concentration, this results were in consistent with the other studies reported earlier in contrast other studies found normal thyroid hormone levels while TSH levels were increased. [30][31][32][33][34] This may be due to CBZ and Phenytoin induces hepatic microsomal enzymes markedly in dose-dependent fashion whereas VAL has no significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, reduced concentrations of serum thyroid hor mones in patients treated with PHT have been reported by several investigators [2][3][4], and the effects of other anticonvulsants on thyroid hormones have also been noted [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%